Microwave ablation of hyperplastic parathyroid glands is a treatment option for end-stage renal disease patients ineligible for surgical resection. (1st January 2019) - Zhuo, Li; Zhang, Ling; Peng, Li-Li; Yang, Yue; Lu, Hai-Tao; Chen, Da-Peng; Li, Wen-Ge; Yu, Ming-An
Abstract: Background: Secondary hyperparathyroidism (SHPT) is a frequently encountered problem in patients with end-stage renal disease (ESRD). Some patients with severe SHPT could not be managed by medical treatment and are ineligible for surgical resection. Purpose: Our objective was to evaluate the efficacy, safety of microwave ablation (MWA) on these patients. Materials and Methods: Between 1 April 2015 and 28 February 2017, 35 patients (M/F 19/16, age 49.8 ± 12.9 years) were enrolled. All patients were treated with MWA. Levels of intact parathyroid hormone (iPTH) and of serum calcium and phosphorus were compared pre- and post-ablation. Repeated-measures ANOVA was used to compare treatment outcomes pre- and post-ablation. Results: Complete ablation was achieved in all 63 glands in the 35 patients with SHPT. The mean follow-up time was 15.9 ± 2.2 months. The maximum gland diameter was 6–31 mm (mean, 14.9 ± 5.5 mm). The trends of the changes in iPTH and calcium levels showed a curve: the level of iPTH and calcium at 6 months post-ablation were lower than those pre-ablation (both p  < .0001); after then iPTH remained relatively stable and the end of follow up, with no rebound ( p  < .0001), while instead of calcium at the end of follow up was not significantly lower than pre-ablation ( p  = .462). The trend in the change in phosphate levels showed a straight line; the level of phosphate at 6 months post-ablation and at the end of follow up both were significantly lower than pre-MWA ( p  < .001). There was no major complication. Conclusions: In this series, MWA was used successfully to treat SHPT patients who are ineligible for surgical resection.